Identification and validation of biomarkers related to nicotinamide metabolic pathway activity in heart failure - Du, Jianping; Yang, Xiaoyu; Wu, Shuxing; Bi, Shuli; Wang, Peng; Cheng, Lisong; Yao, Zhuhua (Frontiers in Genetics, 2025)
BackgroundHeart failure (HF) is the final stage of cardiovascular diseases. Nicotinamide metabolism (NMN) plays a key role in cardiovascular dysfunction. We aimed to explore genes correlated with NM pathway activity (NMRGs) in HF.MethodsHF data were obtained from public databases, and NMRGs were sourced from literature. Weighted gene co-expression network analysis (WGCNA) identified NM-associated module genes. Candidate genes were selected via differential expression profiling and module analysis. Biomarkers were identified using protein-protein interaction (PPI) networks, machine learning, and gene expression validation. Diagnostic efficacy was assessed via nomogram. Functional enrichment, immune infiltration, and drug prediction analyses were performed. Biomarker expression was validated by Reverse Transcription quantitative Polymerase Chain Reaction (RT-qPCR).ResultsAmong 492 candidate genes, NDC1, NUP133, and TRMT11 were validated as biomarkers. The nomogram showed high diagnostic accuracy. Biomarkers were enriched in spliceosome and ubiquitin-mediated proteolysis pathways. Immune infiltration revealed correlations with neutrophils. Potential drugs, including tetradecanoylphorbol acetate, were identified. Biomarker expression was significantly lower in HF.ConclusionNDC1, NUP133, and TRMT11 are NM-related biomarkers in HF, offering insights into HF pathogenesis and therapy.